Green Spirituality in The Qur'an: Integration of Spiritual Values and Environmental Conservation Education - Zulaika; Sahrizal Vahlepi; Warissuddin Soleh; Nor Syahirah Ulfa binti Aliudin (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2025)
This study investigates the concept of Green Spirituality from an Islamic perspective by linking the spiritual values in the Qur’an to environmental conservation efforts. In Islamic teachings, humans serve as khalifah (stewards) who are responsible for maintaining the balance of ecosystems and preventing environmental degradation. Using a qualitative approach with thematic analysis of Qur’anic verses, this study highlights the principles of khilafah (stewardship), amanah (trust), and mizan (balance) as the ethical foundations of Islamic environmentalism. The results indicate that Islamic spiritual values can enhance ecological awareness and promote sustainable practices, such as consumption moderation, resource efficiency, and environmental protection as a form of worship, ultimately contributing to a holistic and sustainable approach to environmental preservation. Green Spirituality offers not only an ethical foundation but also a religious solution in responding to the global environmental crisis. Amid increasing environmental damage caused by human actions, the implementation of Qur’anic values in nature conservation has become an unavoidable urgency. This study recommends the integration of spiritual values into environmental policy, education, and social practices as an effort to cultivate sustainable ecological behavior for future generations. Keywords: Al-Qur’an, Green Spirituality, Environmental Preservation